(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the unique masterpieces created by skilled masters of our people in Central Asia, i.e. calligraphy, and analyzes their unique composition. In particular, valuable information is given about the unique decorative compositions in the mausoleums of Khwaja Ahmed Yassavi and Shahi Zinda in the mausoleums of Kusam ibn Abbas.